Evaluation the effect of eugenol containing temporary fillings on shear bond strength of composite restoration (Mustansiria Dental Journal, 2018)
The purpose of this in-vitro study was to evaluate the effect of eugenol-containingtemporary fillings on shear bond strength of composite to dentin and determine theefficiency of dual bonding technique in improving the bond strength using AdperSingle Bond 2 adhesive with 3M composite. Thirty sound human upper firstpremolars were used in this study. The occlusal surface of each tooth was ground toexpose superficial dentin layer, and then dentin bonding agent was directly appliedonto freshly prepared dentin together with cylinder of 3M composite and light cured(group I, control group). Dentin surface pre-treated with zinc oxide eugenol temporaryfilling, then dentin bonding agent together with a cylinder of 3M composite (group II,single bonding technique). While in group III dentin bonding agent was applied firston the dentin surface and light cured, then zinc oxide eugenol temporary filling wasadded for one week, after removal of temporary filling dentin bonding agent togetherwith 3M composite was applied and light cured (dual bonding technique). The shearbond strength of all the specimens was determined using Zwick universal testingmachine. The results showed that all temporary filling treated groups (II and III) hadlower mean shear bond strength compared to control group (group I), whereascompared to single bonding technique, dual bonding technique significantly increasedthe shear bond strength.